The Effects of Work Motivation and Communication Condition on Elementary Teachers’ Performance - Wage Umami; Rifma Rifma; Syahril Syahril (Universitas Riau, 2021)
This research was aimed at exposing the contribution of working motivation and the communication condition towards the primary teachers’ working performance at Ampek Angkek sub-district of Agam Regency. This research employed quantitative research with correlation design. The population of this research wasprimary public servant teachers at Ampek Angkek sub-district of Agam Regency which were 231 people. The samples were 67 people that were taken through stratified proportional technique random sampling, by considering the strata levels education and working experiences. The instrument used to accumulate the data wastested to check the reliability. The result indicated that the working motivation contributed to the teachers working performance as 35%, communication conditioncontributed as 20,3% to teachers’ working perfomance, and both working motivation and communication condition assigned as 45,6% to teachers’ working performance. It can be concluded that working motivation and communication condition had influenced to primary teachers’ working perfomance at Ampek Angkek sub-district Agam Regency.